Annotated Checklist of the Macrofungi (Fungi: Dikarya) of Pelawan Forest, Bangka Island, Sumatra - Widayanti, Gusti Ayu; Effendi, Zahrial; Sari, Diah Komala; Arifah, Nur; Swandi, Monica Kharisma; Asyavira, Gita Cindy; Iqbal, Muhammad (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
This study provides an annotated checklist of macrofungi in Pelawan Forest, Bangka Island, Indonesia. A total of 59 species of macrofungi from 22 families were documented, highlighting the presence of macrofungi in the area. The families Polyporaceae, Agaricaceae, and Marasmiaceae were the most diverse, accounting for over 50% of the total species recorded. The most common family found was Polyporaceae, with 13 species. Our findings indicate that Pelawan Forest has significant economic potential related to macrofungi, such as species used as food or medicine. This study can serve as a reference for developing effective conservation and management strategies for the forest ecosystem in Bangka Island. Keywords: Bangka Island, biodiversity, Indonesia, macrofungi, Pelawan Forest.